Representasi Budaya Indonesia dalam Buku Teks Bahasa Inggris Sekolah Dasar: Analisis Wacana Kritis. - Fathiyya, Iftikharunnisa'; Mobit, Mobit; Wahyuna, Yuna Tresna (Jurnal Ilmiah Wahana Pendidikan, 2024)
Textbooks are one of the most important media in the English teaching-learning process. It plays a critical role for students and teachers in easing the teaching and learning processes. Using textbooks, teaching and learning processes are expected to run better, because teachers and students are facilitated in building an understanding of the ongoing material. Many subjects are presented in textbooks, such as small things done in daily life, food, movies, or culture from within and outside the country. This research aims to investigate Indonesian culture presented in the sixth-grade elementary English textbook entitled "Stairway: A Fun and Easy English Book.” This study focuses on analyzing one aspect of culture: products represented in the form of images and texts. This study used critical discourse analysis as the research design. The data in this study were obtained by reading the textbook, and the results showed that the textbook provides several Indonesian cultural products. Thus, the textbook writer introduced products commonly produced by Indonesians. Various products are shown by the book provider/writer through images and texts that refer to or discuss particular cultural aspects. There were four visual images and one text, indicating that the image belonged to the cultural aspect of the product. The pictures and text revealed cultural aspects in the form of buildings, clothes (uniform), food, and sports (traditional martial arts).